Bacterial and fungal inhibitor interacted impacting growth of invasive Triadica sebifera and soil N2O emissions - Lai, Xiaoqin; Luo, Laicong; Fang, Haifu; Zhang, Ling; Shad, Nasir; Bai, Jian; Li, Aixin; Zhang, Xi; Yu, Yadi; Wang, Hao; Siemann, Evan (Frontiers in Forests and Global Change, 2023)
Plant invasions affect biodiversity and seriously endanger the stability of ecosystems. Invasive plants show strong adaptability and growth advantages but are influenced by various factors. Soil bacteria and fungi are critical to plant growth and are important factors affecting plant invasions. Plant invasions also affect soil N2O emissions, but the effects of invasive plants from different population origins on N2O emissions and their microbial mechanisms are not clear. In this experiment, we grew Triadica sebifera from native (China) and invasive (USA) populations with or without bacterial (streptomycin) and/or fungal (iprodione) inhibitors in a factorial experiment in which we measured plant growth and soil N2O emissions of T. sebifera. Plants from invasive populations had higher leaf masses than those from native populations when soil bacteria were not inhibited (with or without fungal inhibition) which might reflect that they are more dependent on soil bacteria. Cumulative N2O emissions were higher for soils with invasive T. sebifera than those with a plant from a native population. Bacterial inhibitor application reduced cumulative N2O emissions but reductions were larger with application of the fungal inhibitor either alone or in combination with the bacterial inhibitor. This suggests that fungi play a strong role in plant performance and soil N2O emissions. Therefore, it is important to further understand the effects of soil microorganisms on the growth of T. sebifera and soil N2O emissions to provide a more comprehensive scientific basis for understanding the causes and consequences of plant invasions.